The effectiveness of OIDDE and PBL with liveworksheets on critical thinking skills - Saufa Ulya Fauziah; Muhammad Minan Chusni; Adam Malik (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2026)
Students' critical thinking skills in the topic of simple harmonic vibrations are still relatively low, so a learning model that can optimize these abilities is needed. This study aims to analyze the implementation of learning using the OIDDE Model and Problem-Based Learning (PBL) assisted by Liveworksheets, and to measure the resulting improvement in critical thinking skills. The research method used was a quasi-experimental with a non-equivalent control group design, involving 36 students each in experimental classes I and II. The results showed that the implementation of learning in both models was in the very good category (OIDDE 89% and PBL 85%), and there was a significant increase in critical thinking skills in both models, with an n-gain of 0.73 in experimental class I and 0.71 in experimental class II. Statistical tests showed a difference in critical thinking improvement between the two models. This study indicates that the application of the OIDDE Model provides superior improvement compared to PBL in learning simple harmonic vibrations, making it an effective alternative learning model for developing students' critical thinking skill.